Diet of the European ground squirrel (Spermophilus citellus) in the southern Pannonian plain - Arok, Maja; Nikolić, Tijana; Győri-Koósz, Barbara; Milinski, Lea; Ćirović, Duško (Archives of Biological Sciences, 2021)
Paper description: Abst Overwinter survival of hibernators is influenced by the amount and quality of food consumed during the active season. Microhistological analysis of feces was used to establish the feeding habits of the European ground squirrel (Spermophilus citellus) in northern Serbia, a region that has experienced human-induced environmental changes during the last 7 decades. Whereas a number of different species appear in the diet, there is clear preference for a small number of food categories. Considering the predicted impact of climate change on food availability for this species, its feeding habits should be taken into account when developing habitat management plans. ract: Overwinter survival of hibernators is directly influenced by the fat reserves accumulated during the active season. The European ground squirrel, Spermophilus citellus, an endangered flagship species of the open grasslands of central and southeastern Europe, is no exception. Considering anthropogenic changes affecting its habitats in northern Serbia, we studied the species’ feeding habits by subjecting its feces to microhistological examination. In addition to identifying plant remains in the feces, we examined the vegetation of the four study sites located inside a local mosaic of steppe and saline pastures. Our findings indicate that these remaining European ground-squirrel sites are diverse and stable grasslands covered by native flora that represents a complete dietary base for the species. The diet is dominated by a small number of plant species, specifically Achillea millefolium, legumes and grasses, with sporadic contributions from a number of other species. The diet of S. citellus also differs by location and season in that grasses dominate during the early season, while A. millefolium takes precedence later in the year. This dietary information is essential for the development of future species and habitat management strategies. In light of the predicted impact of climate change on grasslands in northern Serbia, our findings will be instrumental for translocations and conservation actions in the future.